2013
DOI: 10.1128/jvi.01112-13
|View full text |Cite
|
Sign up to set email alerts
|

Age and Immune Status of Rhesus Macaques Impact Simian Varicella Virus Gene Expression in Sensory Ganglia

Abstract: S imian varicella virus (SVV) and varicella-zoster virus (VZV)are neurotropic alphaherpesviruses that establish latency within the sensory ganglia during primary infection. Viral latency is generally characterized by a quiescent state with limited gene expression; for example, during herpes simplex virus (HSV) latency, only the latency-associated transcripts (LATs) are abundantly expressed (1). However, VZV latency can be associated with the transcription of multiple genes, including open reading frames (ORFs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, rapid recovery of CD4 T cells, but not CD8 T cells, after stem cell transplants is associated with reduced rates of cytomegalovirus reactivation (Drylewicz et al , 2016). Previous studies from our lab have also shown a greater role for CD4 T cells in the resolution of acute SVV infection where CD4 depleted animals had higher viral loads, prolonged disease and are unable to establish latency in the ganglia (Haberthur et al , 2011; Meyer et al , 2013). On the other hand, CD8+ cells in the trigeminal ganglia play a critical role in the prevention of HSV-1 reactivation in mice (St Leger and Hendricks, 2011), which indicates that immunological control of reactivation may differ between these two closely related viruses.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, rapid recovery of CD4 T cells, but not CD8 T cells, after stem cell transplants is associated with reduced rates of cytomegalovirus reactivation (Drylewicz et al , 2016). Previous studies from our lab have also shown a greater role for CD4 T cells in the resolution of acute SVV infection where CD4 depleted animals had higher viral loads, prolonged disease and are unable to establish latency in the ganglia (Haberthur et al , 2011; Meyer et al , 2013). On the other hand, CD8+ cells in the trigeminal ganglia play a critical role in the prevention of HSV-1 reactivation in mice (St Leger and Hendricks, 2011), which indicates that immunological control of reactivation may differ between these two closely related viruses.…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, we did not detect alpha/beta interferon transcripts. This may be due to the small number of infected cells and the ability of SVV to suppress interferon expression within those infected cells (143,144), which could have diluted the strength of the IFN signal, especially since we were using total ganglion RNA. IFN-stimulated genes could potentially be upregulated within infiltrating innate immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we identified a point mutation at nucleotide 41990 from G to A within ORF22, producing an amino acid change from valine to isoleucine ( Figure 1B) and a transition of nucleotide 106546 from T to C producing a silent mutation within ORF62/71 ( Figure 1C). The nucleotide change in ORF62/71 was also previously shown in the sequencing of an ORF61 deletion virus that was generated from the same parental SVV cosmid system [11][12][13]. SVV ORF22 is a putative tegument protein based on the function of herpes simplex virus type-1 (HSV-1) UL36 homolog.…”
Section: Whole-genome Analysis Of Svv Bacmentioning
confidence: 73%